Analysis on design parameters of water-lubricated journal bearings under hydrodynamic lubrication. (August 2016) - Gao, Gengyuan; Yin, Zhongwei; Jiang, Dan; Zhang, Xiuli; Wang, Yanzhen
The article aims to investigate the relationship between eccentricity ratio and the Sommerfeld number based on hydrodynamic water-lubricated journal bearings. Considering the differences between water and oil, especially the difference in vapor pressure, the effect of cavitation on pressure distribution of water film is analyzed based on three boundary conditions and a cavitation model by computational fluid dynamics (CFD). The result shows that the three boundary conditions are all not suitable to replace cavitation model in numerical analysis of water-lubricated journal bearings. Then numerical analysis of journal bearings with different dimensions is undertaken with the cavitation model under different working conditions. Based on the analysis, a reference is produced for designing water-lubricated journal bearings under hydrodynamic lubrication. At last, the reference is verified by experiments.